A national study of the relationship of care site HIV specialization to early adoption of highly active antiretroviral therapy. - Wilson, Ira B; Landon, Bruce E; Ding, Lin; Zaslavsky, Alan M; Shapiro, Martin F; Bozzette, Samuel A; Cleary, Paul D (Medical care, 2005)
Little is known about characteristics of organizations that predict early adoption of highly active antiretroviral therapy (HAART) for persons with HIV infection.
Keywords: Adult; Ambulatory Care; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Medicine; Physician's Practice Patterns; Quality of Health Care; Specialization; United States